The Circ_0001367/miR-545-3p/LUZP1 Axis Regulates Cell Proliferation, Migration and Invasion in Glioma Cells - Dong, Xuchen; Zhang, Peng; Liu, Liang; Li, Haoran; Cheng, Shan; Li, Suwen; Wang, Yuan; Zheng, Chaonan; Dong, Jun; Zhang, Li (Frontiers in Oncology, 2021)
Glioma is the most common primary intracranial malignant tumour in adults. It has a high incidence and poses a serious threat to human health. Circular RNA is a hotspot of cancer research. In this study, we aimed to explore the role of circ_0001367 in gliomagenesis and the underlying mechanism. First, qRT-PCR was conducted, which showed that circ_0001367 level was downregulated in glioma tissues and cells. Next, gain-of-function and loss-of-function assays were performed, which indicated that circ_0001367 inhibited the proliferation, migration and invasion of glioma cells. Subsequent bioinformatics analysis, dual-luciferase reporter assays, RNA immunoprecipitation assays and cell function assays demonstrated that circ_0001367 inhibited the proliferation, migration and invasion of glioma cells by absorbing miR-545-3p and thereby regulating the expression of leucine zipper protein (LUZP1). Finally, an in vivo experiment was conducted, which demonstrated that circ_0001367 inhibited glioma growth in vivo by modulating miR-545-3p and LUZP1. Taken together, the results of this study demonstrate that the circ_0001367/miR-545-3p/LUZP1 axis may be a novel target for glioma therapy.